Rancang Bangun Aplikasi Pelayanan Administrasi Perawatan Sepeda Motor Di PT.Surapita Unitrans Surabaya - Mahendra, Abner; Wurijanto, Tutut; Sulistiowati, Sulistiowati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract : PT. Surapita Unitrans constitute a service company that handles process Kawasaki motorcycle. In handling process motorcycle vehicle maintenance there are some problems that occur in the company, namely the customer can't information scedule queue service, no booking service for customers who have a solid rushing, there is no information available for customer, and in preparing reports to the section of After Sale still using MS Office.From the above problems, then be made a system design aplication administration service motorcycle in PT. Surapita Unitrans which can be set queue service customer automatically by using method Shortest Job First, there is booking service system available for customer, and system can provide information service form history service available for customer, and there is a reporting system for the division after sale.Based on trial results application system administration services made This application can help companies in addressing the queue automatically, generating system booking services for customer, produce history service so that customers can obtain the required information service, and there is reporting period for division After Sale.